Urban transformations and public health in the emergent city - Keith, Michael; de Souza Santos, Andreza Aruska (Global Urban Transformations, 2020)
Urban transformations and public health in the emergent city examines how urban health and wellbeing are shaped by migration, mobility, racism, sanitation and gender. Adopting a global focus, spanning Africa, Asia, Europe and Latin America, the essays in this volume bring together a wide selection of voices that explore the interface between social, medical and natural sciences. This interdisciplinary approach, moving beyond traditional approaches to urban research, offers a unique perspective on today's cities and the challenges they face. Edited by Professor Michael Keith and Dr Andreza Aruska de Souza Santos, this volume also features contributions from leading thinkers on cities in Brazil, China, South Africa and the United Kingdom. This geographic diversity is matched by the breadth of their different fields, from mental health and gendered violence to sanitation and food systems. Together, they present a complex yet connected vision of a 'new biopolitics' in today's metropolis, one that requires an innovative approach to urban scholarship regardless of geography or discipline. This volume, featuring chapters from a number of renowned authors including the former deputy mayor of Rio de Janeiro Luiz Eduardo Soares, is an important resource for anyone seeking to better understand the dynamics of urban change. With its focus on the everyday realities of urban living, from health services to public transport, it contains valuable lessons for academics, policy makers and practitioners alike.